Investigation into the immediate effect of ankle taping on temporal spatial gait parameters and affected ankle kinematics in ambulant adult hemiplegic patients - Al-Talahma, Mohammad Y. M. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScPhysio)--Stellenbosch University, 2012